2020
DOI: 10.1002/aur.2310
|View full text |Cite
|
Sign up to set email alerts
|

DNAMethylation Associated with Mitochondrial Dysfunction in a South African Autism Spectrum Disorder Cohort

Abstract: Autism spectrum disorder (ASD) is characterized by phenotypic heterogeneity and a complex genetic architecture which includes distinctive epigenetic patterns. We report differential DNA methylation patterns associated with ASD in South African children. An exploratory whole‐epigenome methylation screen using the Illumina 450 K MethylationArray identified differentially methylated CpG sites between ASD and controls that mapped to 898 genes ( P ≤ 0.05) which were enriched for nine cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 92 publications
0
45
0
Order By: Relevance
“…ASD is probably the result of a genetic predisposition and epigenetic mechanisms. The work of Stathopoulos et al [48] showed how the methylation of mitochondrial DNA plays an important role in the etiology of ASD. Therefore, understanding the mitochondrial mechanisms involved in ASD could be important for the identification of new targets in the treatment of pathology.…”
Section: Discussionmentioning
confidence: 99%
“…ASD is probably the result of a genetic predisposition and epigenetic mechanisms. The work of Stathopoulos et al [48] showed how the methylation of mitochondrial DNA plays an important role in the etiology of ASD. Therefore, understanding the mitochondrial mechanisms involved in ASD could be important for the identification of new targets in the treatment of pathology.…”
Section: Discussionmentioning
confidence: 99%
“…BCAAs provide nitrogen to the glutamate-glutamine cycle and have been implicated as important regulators of glutamatergic neurotransmission (82), which contribute to ASD aetiology (83). Two metabolites (3-H-3-MGA and 3-methylglutaconic acid (3-MGA)) were significantly elevated in our ASD cohort (22) and are characterized as urinary biomarkers of mitochondrial respiratory chain deficiencies (75,84). Altered BCAA metabolism has also been linked to oxidative stress resulting from perturbed NAD + /NADH redox ratios (85).…”
Section: Discussionmentioning
confidence: 91%
“…The observation that congenital errors of mitochondrial metabolism contribute to > 5% of ASD cases (17) first implied a role for mitochondrial dysfunction in ASD. This has since been supported by clinical (18), biochemical (19,20), molecular (21) and more recently, epigenetic data (22). Citrigno et al (23) comprehensively reviewed the recent experimental data that support the Mitochondrial Dysfunction Hypothesis in ASD.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Aging Pcdh clusters Differential methylation Rakyan et al, 2010;Bell et al, 2012;Salpea et al, 2012;Hannum et al, 2013;McClay et al, 2014;Slieker et al, 2016;Kim et al, 2018a Alzheimer's disease Pcdhγc5 Altered expression Li et al, 2012(rat) Li et al, 2017 Pcdh clusters Altered expression Nativio et al, 2018Meyer et al, 2019 Antipsychotic medication Pcdh clusters Differential methylation Melka et al, 2014;Nakazawa et al, 2017 Autism Pcdhα cluster SNP Anitha et al, 2013 Pcdh clusters De novo mutations Iossifov et al, 2014 Pcdh clusters SNV, CNV Krumm et al, 2015 Pcdhα12 Differential methylation Stathopoulos et al, 2020 Bipolar disorder Pcdh clusters Association Hong et al, 2004;Herzberg et al, 2006 Pcdhα cluster SNP Pedrosa et al, 2008 Child Schwab et al, 1997;Straub et al, 1997;Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014;Pardinas et al, 2018;Walker et al, 2019 Pcdh clusters 3D genome Rajarajan et al, 2018 Pcdh clusters Altered Pcdh pathway Shao et al, 2019 Pcdhα7, α8 Altered expression Hall et al, 2020Hall et al, et al, 2018. Interestingly, APOE4, a prominent genetic risk allele for late-onset AD, causes cPcdh gene upregulation in iPSCderived cerebral organoids (Meyer et al, 2019).…”
Section: Gene Alteration Referencesmentioning
confidence: 99%